Whole-Body ARHGAP21-Deficiency Improves Energetic Homeostasis in Lean and Obese Mice - Soares, Gabriela Moreira; Zangerolamo, Lucas; Costa-Júnior, Jose Maria; Vettorazzi, Jean Franciesco; Carneiro, Everardo Magalhães; Saad, Sara Teresinha; Boschero, Antonio Carlos; Barbosa-Sampaio, Helena Cristina (Frontiers in Endocrinology, 2019)
Inhibition of Rab-GAP TBC1 domain family member 1 (TBC1D1) reduces body weight and increases energy expenditure in mice. Here, we assessed the possible involvement of GTPase activating protein 21 (ARHGAP21), a Rho-GAP protein, in energy homeostasis. Wild-type and whole-body ARHGAP21-haplodeficient mice were fed either chow or high-fat diet for 10 weeks. These mice were analyzed for body weight, food intake, voluntary physical activity and energy expenditure by indirect calorimetry. Real-time PCR was performed to determine changes in the expression of hypothalamic-anorexic genes. Whole-body ARHGAP21-haplodeficient mice showed lower body weight and food intake associated with increased energy expenditure. These mice also showed higher expression of hypothalamic-anorexic genes such as POMC and CART. Our data suggest that the reduction in body weight of ARHGAP21-haplodeficient mice was related to alterations in the central nervous system. This suggests a new role for ARHGAP21 in energetic metabolism and prompts us to consider GAP protein members as possible targets for the prevention and treatment of obesity and related diseases.